Apoptosis in Cancer Pathogenesis and Anti-cancer Therapy New Perspectives and Opportunities - Gregory, Christopher D. (Advances in Experimental Medicine and Biology, 2016)
This book discusses properties of apoptosis and other cell death modalities in cancer pathogenesis and treatment. Its nine chapters discuss modulation of anti-tumor inflammatory and immune responses, effects on the tumor microenvironment, to strategies for improving pro-apoptotic therapies, mechanisms and implications for disease pathogenesis, axl and mer receptor tyrosine kinases, immunogenic apoptotic cell death and anti-cancer immunity and cancer cell death-inducing radiotherapy. This book places the onco-biology of apoptosis in clear and objective perspective through an expertly synthesized series of reviews. Apoptosis in Cancer Pathogenesis and Anti-cancer Therapy is a deft and thorough exploration of cutting-edge research in apoptosis and anti-cancer mechanisms from basic biology to oncology. It highlights a rapidly growing field within cancer research and is essential reading for oncologists, biochemists and advanced graduate students alike.